The buffering effects of positive emotion on the relationship between interpersonal conflict and relationship damage: A moderated mediation study - Oh , Sunyoung; Suh, Youngwon (Korean Journal of Industrial and Organizational Psychology, 2015)
The purpose of the present research was to examine the buffering effects of positive emotion on the relationship between interpersonal conflict and relationship damage. The present research proposed the moderated mediation model in which perceived interactional injustice from the other party in conflict situations has an effect on relationship damage via residual emotion, and the strength of the mediation effect is weakened by the experience of positive emotion. Results from a sample of 215 participants showed that the strength of the mediated effects of perceived injustice on relationship damage through residual emotion was weaker at higher levels of positive emotion than at lower levels of positive emotion. These findings support the buffering effects of positive emotion on the relationship between perceived injustice in conflict and relationship damage, suggesting that the experience of positive emotion can serve as a protective factor against the negative effect of interpersonal conflict on relationship maintenance. The discussion focuses on implications of the findings in terms of conflict management, limitations and suggestions for future research.